Vortex dynamics in Bi2Sr2CaCu2O8+δ single crystals with planar defects - Herbsommer, J.A.; Correa, V.F.; Nieva, G.; Pastoriza, H.; Luzuriaga, J.; Correa, Víctor Félix; Nieva, Gladys (Elsevier, 2001)
Fil: Herbsommer, J.A. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina